Chromium speciation in leather samples: an experiment using digital images, mobile phone and environmental concepts - Costa, Vinícius; Neiva, Ariane; Pereira-Filho, Edenir (Eclética Química, 2019)
This study proposes a new and simple method for Cr speciation and Cr(VI) determination in leather samples using digital images. The experiments were performed using a mobile phone and a free app called PhotoMetrix that was used to obtain and process data. The results obtained from PhotoMetrix were compared to reference methods using UV−Vis spectroscopy. A statistical evaluation between both proposed and the reference methods using two-sample t-test did not show a significant difference at a 95% confidence level. Bovine leather samples (4 samples) tanned with Cr salts and ovine leather samples (3 samples) tanned with vegetable tannin were analyzed. The proposed method presented limits of detection (LOD) and quantification (LOQ) of 0.6 and 2 mg/kg, respectively. In addition, the proposed method using PhotoMetrix and digital images can provide undergraduate students an opportunity to learn topics such as quantitative analyses, environmental chemistry, speciation chemistry, image processing and treatment of statistical data. The results demonstrated that the proposed method can be applied to routine analyses and in experimental analytical chemistry courses.